Influence of post-exercise hypoxic exposure on hepcidin response in athletes - Badenhorst, C. E.; Dawson, B.; Goodman, C.; Sim, M.; Cox, G. R.; Gore, C. J.; Tjalsma, H.; Swinkels, D. W.; Peeling, P. (European Journal of Applied Physiology, 2014)
Purpose To assess the influence of a simulated altitude exposure (~2,900 m above sea level) for a 3 h recovery period following intense interval running on post-exercise inflammation, serum iron, ferritin, erythropoietin, and hepcidin response. Methods In a cross-over design, ten well-trained male endurance athletes completed two 8 × 3 min interval running sessions at 85 % of their maximal aerobic velocity on a motorized treadmill, before being randomly assigned to either a hypoxic (HYP: F IO2 ~0.1513) or a normoxic (NORM: F IO2 0.2093) 3 h recovery period. Venous blood was collected pre- and immediately post-exercise, and after 3 and 24 h of recovery. Blood was analyzed for interleukin-6, serum iron, ferritin, erythropoietin, and hepcidin. Results Interleukin-6 was significantly elevated (p < 0.01) immediately post-exercise compared to baseline (NORM: 1.08 ± 0.061 to 3.12 ± 1.80) (HYP: 1.32 ± 0.86 to 2.99 ± 2.02), but was not different between conditions. Hepcidin levels were significantly elevated (p < 0.01) at 3 h post-exercise for both conditions when compared to baseline (NORM: 3.25 ± 1.23 to 7.40 ± 4.00) (HYP: 3.24 ± 1.94 to 5.42 ± 3.20), but were significantly lower (p < 0.05) in the HYP trial compared to NORM. No significant differences existed between HYP and NORM for erythropoietin, serum iron, or ferritin. Conclusion Simulated altitude exposure (~2,900 m) for 3 h following intense interval running attenuates the peak hepcidin levels recorded at 3 h post-exercise. Consequently, a hypoxic recovery after exercise may be useful for athletes with compromised iron status to potentially increase acute dietary iron absorption.